(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study is motivated by the low motivation to learn and skills to write speech scripts in grade XI students of SMK Negeri 15 Garut. There is a gap between conventional learning methods that are less attractive and the need for an interactive approach that can increase student participation. The purpose of this study is to determine the effectiveness of the application of ClassPoint interactive learning media in improving students' motivation and writing skills. This study uses a quantitative approach with a quasi-experimental non-equivalent control group design. The sample consisted of two classes with a total of 28 students each. The experimental class uses ClassPoint, while the control class uses conventional methods. The instruments used included a learning motivation questionnaire and a writing skill test. The results of the analysis showed that the implementation of ClassPoint significantly improved students' motivation and writing skills. The average normalized gain for writing skills in the experimental class was 0.48 (medium category), while the control class only reached 0.12 (low category). Thus, it can be concluded that the use of ClassPoint interactive learning media is effective in increasing learning motivation and speech writing skills among grade XI students.